Cidade Morada Amiga no Oeste do Paraná: memórias das tensões em Assis Chateaubriand/PR (1960/2010) - Silva, Márcia Cristina Rodrigues da (2011)
The present essay has the purpose of discussing the resignifications memory occurred in Assis Chateaubriand, Paraná West. It relies on public memory in the 1990s produced from the crystallization of a homogeneous memory and its disruptions. We seek to think and discuss other memories in dispute in this case. We address initially the effort made by the government, especially in the administration of Luiz Amaral (1993-1996), who sought to build a single story to the city, from memories belonging to groups "winners", expressing that want projects provide for the municipality. Sought from other memories, understand what is minimized in memories "public", and the groups that were planted renegades to that memory and worshiped. Articulating interpretations of oral sources, written and journalistic materials, we seek to understand disputes over the formation of memories of Assis Chateaubriand, which occurred in the late 1950 and early 1960. We also observed that reframes articulate these memories, especially in 1990, during the second round of elections to the state government of Parana, when memories were appropriate, cooled, and re-signified in the public sphere, resurfacing in the state, to unearth the past "troublemaker" in the city that tried to be shown as "dwelling friend"